PENGARUH MODEL PEMBELAJARAN RADEC (READ, ANSWER, DISCUSS, EXPLAIN, CRETAE) TERHADAP KEMAMPUAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VIII SMP NE GERI 1 KUALASIMPANG TAHUN AJARAN 2024/2025 - Fathiah Riadianti; Atika Wasilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of using the RADEC (Read, Answer, Discuss, Explain, Create) learning model on the ability to write observation report texts of class VIII students of SMP Negeri 1 Kualasimpang. The method used is experimental research. The population of this study was all class VIII students of SMP Negeri 1 Kualasimpang, totaling 256 students. The sampling technique used purposive sampling with 2 classes selected, namely class VIII-I (32 students) as the experimental class and class VIII-3 (32 students) as the control class. Data collection was carried out by observation, documentation, interviews and tests. Inferential statistical data analysis was carried out by normality test, homogeneity test and hypothesis test. The results of the analysis showed that there was an effect of the RADEC model on the ability to write observation report texts of class VIII students of SMP Negeri 1 Kualasimpang with df = n-2 or df = 64 - 2 = 62, obtained ttable of 1.997. It is known that tcount > from ttable 14.001 > 1.997 at a significance level (a) of 5%, so H0 is rejected and Ha is accepted. This shows that there is an influence of the RADEC learning model on the ability to write observation report texts of class VIII students of SMP Negeri 1 Kualasimpang in the 2024/2025 academic year.